Production of Hydroxyapatite (HAp) nanoparticles by wet chemistry method for biomedical usage - Taufiq Aminullah Bin Mokhtar (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Hydroxyapatite, (HAp), Ca10(PO4)6(OH)2, is a physically occuring mineral found in the inorganic component of human bone and enamel . The basic elements of HAp are mainly calcium and phosphorous, with a stoichiometric to calcium to phosphorous ratio of 1.67 capable of promoting intimate bone growth onto femoral implants. HAp is rendered a bioactive material since it has the ability to promote such growth with rapid fixation in what is also considered an osteoconductive process. The present study aims to produce HAp powders via the wet chemical precipitation technique, in order to evaluate the critical process parameters (mixing temperature, stirring rate, and Ca/P molar ratio) and their effect ( main and interaction) on controlling the final HAp powder characteristics, such as, phase composition, crystallinity, crystallite size and particlesize.